HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN INTENSITAS BERMAIN GAME ONLINE SISWA SMP NEGERI 1 TALAGA JAYA KABUPATEN GORONTALO - Rahmawaty Parman; Firman Pakaya (program studi psikologi, 2022)
This research aims to determine the relationship between emotional intelligence and the intensity of playing online games in SMP Negeri 1 Talaga Jaya students who play online games. The research is a quantitative research with a research population of 59 students. The research subjects were determined based on the subject criteria set by the researcher, namely, students at SMP Negeri 1 Talaga Jaya who played online games with a duration of playing games more than 3 hours per day. The sample was taken using a purposive sampling technique where a researcher determines the subject with several criteria. Data collection is done by distributing questionnaires to respondents. The analysis used in this research is product moment correlation. The results of the hypothesis test obtained are the correlation coefficient r = -0.256 with a significance (p) = 0.050 (p<0.05) Means Ha is accepted, therefore can be concluded there is a negative relationship between emotional intelligence and online game addiction in SMP Negeri 1 Talaga students. Jaya. The higher the emotional intelligence, the lower the intensity of playing online games, and conversely the lower the emotional intelligence, the higher the intensity of playing online games, even though the degree of relationship between the two variables is relatively weak